Comparative assessment of structural and tear film alterations in rabbit meibomian gland dysfunction models using chemical and electrocauterization techniques - Deeksha Prasad; Saumya Jakati; Kiran Kumar Bokara; Sayan Basu; Vivek Singh; Pragnya Rao Donthineni (Scientific Reports)
Abstract Meibomian gland dysfunction (MGD) constitutes the most common cause of dry eye disease (DED), where altering meibum or lipids result in tear film instability. This study compares structural and tear film changes induced by chemical cauterization (CC) and electrocauterization (EC) in establishing a rabbit model of obstructive MGD assessed using non-invasive tear film assessment and histology. Eighteen New Zealand white rabbits were subjected to CC (n = 9) using 1 M NaOH-soaked sponges or EC (n = 9) using electrocautery probes. Non-invasive tear film assessment including tear meniscus height, non-invasive tear film break-up time (NITBUT), and meibography were performed using keratography 5 M (Oculus, Germany) at days 7, 14, 30, 60, and 90 and structural changes were assessed by histopathological, IHC studies, and qPCR. Both groups showed similar clinical features, including increased lid margin vascularity, irregularity, and MG orifice plugging by day 30. NITBUT significantly decreased by day 30 and persisted at day 90 (CC: 9.50 ± 0.37, p = 0.002; EC: 8.34 ± 0.48, p = 0.008), indicating tear film instability. CS scores were higher at day 90, and average meiboscore was 2.0 ± 1.0 (CC, p = 0.03) and 1.7 ± 0.6 (EC, p < 0.01). Histopathology confirmed duct dilatation, inspissated secretions, and acinar atrophy. IHC showed decreased CK-14 expression. Gene expression for proliferation and lipid synthesis was similar between groups. In conclusion, this study demonstrates that CC and EC effectively induce obstructive MGD in rabbits, with measurable changes on non-invasive tear film assessments, meibography, and histology as seen in humans. Non-invasive assessments can provide standardized, objective metrics for studying DED in animal models and evaluating therapeutic interventions.